Drastic difference between hole and electron injection through the gradient shell of CdxSeyZn1−xS1−y quantum dots. Issue 34 (18th August 2017) - Abdellah, Mohamed; Poulsen, Felipe; Zhu, Qiushi; Zhu, Nan; Žídek, Karel; Chábera, Pavel; Corti, Annamaria; Hansen, Thorsten; Chi, Qijin; Canton, Sophie E.; Zheng, Kaibo; Pullerits, Tõnu
Abstract : Ultrafast fluorescence spectroscopy was used to investigate the hole injection in Cd x Se y Zn1− x S1− y gradient core–shell quantum dot sensitized NiO photocathodes. Abstract : Ultrafast fluorescence spectroscopy was used to investigate the hole injection in Cd x Se y Zn1− x S1− y gradient core–shell quantum dot (CSQD) sensitized p-type NiO photocathodes. A series of CSQDs with a wide range of shell thicknesses was studied. Complementary photoelectrochemical cell measurements were carried out to confirm that the hole injection from the active core through the gradient shell to NiO takes place. The hole injection from the valence band of the QDs to NiO depends much less on the shell thickness when compared to the corresponding electron injection to n-type semiconductor (ZnO). We simulate the charge carrier tunneling through the potential barrier due to the gradient shell by numerically solving the Schrödinger equation. The details of the band alignment determining the potential barrier are obtained from X-ray spectroscopy measurements. The observed drastic differences between the hole and electron injection are consistent with a model where the hole effective mass decreases, while the gradient shell thickness increases.